Central neurocytoma in the vermis of the cerebellum - Kapoor Neelkamal; Gandhi Ajay; Chaurasia A (Indian Journal of Pathology and Microbiology, 2009)
In neuropathology, anatomic landmarks and topographic relationships bear particularly on issues of differential diagnosis. A case of central neurocytoma of the vermis of the cerebellum is being reported in this article. A 45-year-old male with features of hydrocephalous and a posterior fossa space-occupying lesion was diagnosed as having central neurocytoma upon a microscopy of Hematoxylene and Eosin stained sections. The diagnosis was confirmed by a positive immunohistochemical reaction for Neuron Specific Enolase (NSE) and Synaptophysin. This case report is being made to emphasize that a high index of suspicion is required even for reporting neuropathology where the site does not match the conventional location of the lesion seen and also to emphasize the importance of immunohistochemistry in proving such unusually located lesions